Altering phosphoinositides in high‐fat diet‐associated prostate tumor xenograft growth. Issue 4 (28th October 2021) - Huang, Mingguo; Koizumi, Atsushi; Narita, Shintaro; Nakanishi, Hiroki; Sato, Hiromi; Kashima, Soki; Nara, Taketoshi; Kanda, Sohei; Numakura, Kazuyuki; Saito, Mitsuru; Satoh, Shigeru; Nanjo, Hiroshi; et al.
Abstract: The metabolic reprogramming of phospholipids may affect intracellular signal transduction pathways. A high‐fat diet (HFD) is attributed to prostate cancer (PCa) progression, but the expression pattern and role of phospholipids in HFD‐mediated PCa progression remains unclear. In this study, HFD enhanced LNCaP xenograft tumor growth by upregulating the phosphatidylinositol (PI) 3‐kinase (PI3K)/AKT signaling pathway. A lipidomic analysis using xenograft tumors showed that phosphoinositides, especially PI (3, 4, 5)‐trisphosphate (PIP3 ), including several species containing C38:4, C38:3, and C40:4 fatty acids, increased in the HFD group compared to control. Fatty acid synthase (FASN) was significantly upregulated in xenograft tumors under HFD in both gene and protein levels. PCa cell growth was significantly inhibited through the decreased AKT signaling pathway by treatment with cerulenin, a chemical FASN inhibitor, which also downregulated PIP, PIP2, and PIP3 but not PI. Thus, dietary fat influences PCa progression and alters phosphoinositides, especially PIP3, a critical player in the PI3K/AKT pathway. These results may offer appropriate targets, such as FASN, for dietary intervention and/or chemoprevention to reduce PCa incidence and progression. Abstract : HFD‐induced alteration of PIPs, especially PIP3, may activate proliferative signaling transduction, such as the PI3K/AKT pathway through the upregulation of FASN, and influence PCa progression. Therefore, PI3K/AKT signaling and FASN could be the important targets for dietary intervention and/or chemoprevention in PCa incidence and progression.